2003
DOI: 10.2138/am-2003-2-314
|View full text |Cite
|
Sign up to set email alerts
|

Biotite dissolution processes and mechanisms in the laboratory and in nature: Early stage weathering environment and vermiculitization

Abstract: Despite the relatively small abundance of biotite [7.6% of the exposed continental crust surface (Nesbitt and Young 1984)], biotite weathering is important because it is a source of K for plant nutrition and a major source of Fe and Mg in ground water (e.g., Berner and Berner 1996).The dissolution of minerals is generally explained by protonation, deprotonation, and the subsequent detachment of metal species (e.g., Stumm 1992) based on laboratory experiments under "far from equilibrium" conditions. Surface com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 30 publications
7
53
0
Order By: Relevance
“…Pits have circular form and appear randomly distributed over the surface. This confirms previous work on silicate alteration (Zuddas and Michard, 1993;Murakami et al, 2002;Aldushin et al, 2006), where dissolution effects on the surface state were found from the very early stages of the process. However, the relationship between the measured dissolution fluxes and surface changes is unclear.…”
Section: Evolution Of the Surface Statesupporting
confidence: 91%
“…Pits have circular form and appear randomly distributed over the surface. This confirms previous work on silicate alteration (Zuddas and Michard, 1993;Murakami et al, 2002;Aldushin et al, 2006), where dissolution effects on the surface state were found from the very early stages of the process. However, the relationship between the measured dissolution fluxes and surface changes is unclear.…”
Section: Evolution Of the Surface Statesupporting
confidence: 91%
“…Th ese symptoms are aff ected by several factors such as time; rate and degree of hydrolysis cycles, ageing conditions dominated pH and chemical environments, as reported by (Taylor, 1987), where all Fe oxides can form under humid conditions in all climatic zones as reviewed before (Segalen, 1971), or may be present as an essential component of kaolin group (Newman and Brown, 1987). In our case, Fe oxides are precipitated mostly at the edges of stone surfaces as a direct result of natural weathering and dissolution processes aff ecting some iron bearing compounds such as biotite grains especially with the presence of some of severe oxidation and hydration cycles, where air and water break down ferrous silicate as biotite and convert their ferrous iron to ferric oxide Red spots, thus changing the original colors to red or brown ones as discussed before by (Murakami et al, 2003;Murakami, et al, 2004). Furthermore, iron which was expelled from the biotite lattice was not removed from the grain in early stages of weathering and interlamellar crystallization of iron oxyhydroxide could take place.…”
Section: Discussionmentioning
confidence: 67%
“…The weathering of pyrrhotite and biotite in the schist produced a visible secondary mineral phase (ocherous precipitate) in the Type III cells after the pH dropped below 4.5, although this precipitate dissolved at a later date. The precipitate likely was jarosite ([KFe 3 (SO 4 ) 2 (OH) 6 ]; Equation (6)), which is indicative of the dissolution of biotite (K and additional Fe source), Fe 2+ to Fe 3+ oxidation, and an acidic environment [6,[51][52][53][54][55]. Formation of jarosite is an indication of incongruent dissolution of biotite (release of more easily removed elements such K).…”
Section: Sulfide Oxidation and Acid Consumption By Al-bearing Mineralsmentioning
confidence: 99%